Direct substitution of secondary and tertiary alcohols to generate sulfones under catalyst- and additive-free conditions - Liu, Yanan (2020)
An environmentally benign protocol that affords propargylic sulfones containing highly congested carbon centers from easily accessible alcohols and sulfinic acids with water as the only byproduct is reported. The reaction proceeded via an in situ dehydrative cross-coupling process by taking advantage of the synergetic actions of multiple hydrogen bonds rather than relying on an external catalyst and/or additives to achieve high product distribution.